2010
DOI: 10.4253/wjge.v2.i10.325
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumors of the small bowels are on the rise: Early aspects and management

Abstract: Neuroendocrine tumors of the small bowel are on the rise. In the US they have increased by 300%-500% in the last 35 years. At the same time their prognosis is much improved. Today, most neuroendocrine tumors (NETs) of the duodenum are detected "incidentally" and therefore recognized at an early stage. Duodenal NETs which are well differentiated, not larger than 10 mm and limited to the mucosa/submucosa can be endoscopically resected. The management of duodenal NETs ranging between 10 and 20 mm needs an interdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 75 publications
(187 reference statements)
4
76
1
8
Order By: Relevance
“…This is possibly because high-resolution imaging, endoscopic diagnosis, and immunohistochemical evaluation in conjunction with histopathological diagnosis are being more frequently used in regular clinical practice [5,6]. However, the therapeutic approach in D-NETs is not fully standardized [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly because high-resolution imaging, endoscopic diagnosis, and immunohistochemical evaluation in conjunction with histopathological diagnosis are being more frequently used in regular clinical practice [5,6]. However, the therapeutic approach in D-NETs is not fully standardized [7].…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of the years 1999-2004, Strosberg et al reported a 5-year survival rate of about 75% in patients with metastatic NET/carcinoid disease of the small intestine, receiving multimodal therapy [17] . An earlier detection of all NETs of the small bowel may have led to improved prognosis [15,18] , since the proportion of advanced disease of small intestine NETs (at the time of diagnosis) has decreased from 31.3% in the 1970s and 1980s, to 22.4% in the 1990s and finally to < 18.9% in the years between 2002-2004 [7,16,20,27] . With duodenal NETs/carcinoids, distant metastases are nowadays observed in less than 6%-10% of the cases [19,20,28,29,30] .…”
Section: Prognosis Of Nets/carcinoids Of the Small Bowelmentioning
confidence: 99%
“…7 mm measuring NET/carcinoid of the rectum (D2). Modified from reference [13][14][15] . NETs: neuroendocrine tumors; EUS: Endoscopic ultrasound.…”
Section: Stomach Duodenum and Rectummentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal NETs are increasing (7); in the USA, the prevalence and the incidence of gastrointestinal NETs have been calculated to be 35/100,000 and 5/100,000, respectively (4), revealing a 7-fold increase in the last 35 years. This phenomenon may partly reflect the increased number of diagnoses of benign and incidentally-identified lesions due to the increased availability of advanced endoscopic and radiological imaging (8)(9)(10). The overall 5-year survival rate for patients with gastrointestinal NETs has improved by almost 20% in the past 35 years (1,11,12).…”
Section: Introductionmentioning
confidence: 99%